PELAKSANAAN INTEGRASI KEILMUAN PADA PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN ILMU KEGURUAN INSTITUT AGAMA ISLAM NEGERI PALOPO - Jumrah123; Baderiah; Alimuddin (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
This research discusses the implementation of knowledge integration in the Islamic Education Management Study Program, Tarbiyah Faculty and Palopo State Islamic Institute.. The research is aimed at: To learn about the integration of sciences in Islamic education management program of the tarbiyah faculties and the sciences of the religious institute of Islam of the state of palopo; To know the supporters and inhibitors of integration in the program of studies of the management of islamic education of the Tarbiyah faculty and of the science of the religion of Islam Institute of the Palopo state. The type of research used is qualitative research. The subjects of this research are Deputy Dean II of FTIK, Head of Study Program, Lecturer, and Student. Research data is obtained through interviews, documentation, and observations with data analysis using processing/naming of raw materials, data sorting based on the result of rewriting, data encoding according to information characteristics, data coherence interrogation analytically, identification of meaning relationships between data from one to the other, data transposition in chart form, meaning display and rewrite about meaning display. The results of this research explain that the implementation of integration of science has been implemented which is seen on RPS, learning materials, and the use of appropriate methods. The integration of science in Islamic Education Management has long been triggered by the leadership, which then the new leadership continued the program in accordance with the vision of mission both in the institution, faculty, and vision of the mission of the study program. Supporting Factors consist of; Human Resource Quality Factors and Government Policy Factors; and inhibitory factors consisting of; Budgetary constraints; teaching materials; means and supplies; and guidelines in the implementation of the integration of science into the Islamic Education Management curriculum.